Kooperatif Tipe Think Pair Share terhadap Hasil Belajar Tematik Siswa Sekolah Dasar - POPIYANTO, YUDHA (Fakultas Bahasa dan Sains, Universitas Wijaya Kusuma Surabaya, 2019)
Cooperative type Think Pair Share is learning that prioritizes ways of cooperating or grouping and opportunities for students to be more active and interactive to foster the courage of students to think and respect the opinions of other students, thus fostering students' confidence in expressing opinions and answering teacher questions verbally or in writing in the thematic learning process in Elementary School (SD). Cooperative objectives of the Think Pair Share type improve thematic learning outcomes to meet and exceed the value of the Minimum Completion Criteria (KKM) of elementary school (SD) students. This research approach uses quantitative and experimental research types, carried out systematically, logically, and thoroughly in a controlled conditioning process. Quasi control group design experimental design through cooperative type Think Pair Share on thematic learning outcomes of third grade students of SDN 2 Kedamean Gresik Regency. The results of the study obtained conclusions of the test results of the independent sample t-test obtained were 0.003 <0.05. Thus, H0 is rejected and Ha is accepted, which means that there is a cooperative influence of the Think Pair Share type on the thematic learning outcomes of the students of SDN 2 Kedamean, Gresik Regency.